Data Prediction Model Based on LSTM Neural Network in Bridge Health Monitoring System. Issue 1 (February 2021) - Xiao, Shihui; Qiao, Shengfang; Chen, Hang; Liu, Xi; Li, Yue; Tang, Mengxiong; Hu, Hesong; Li, Gaotang
Abstract: The abnormal value was common in bridge health monitoring system. The prediction model based on LSTM neural network in bridge health monitoring system was studied in this paper. The modeling process was discussed about LSTM neural network model. The LSTM neural network model was also used to analysis the actual data in bridge. The results indicated that the prediction accuracy of LSTM model was high. Thus, the LSTM neural network could be used to analyze and predict data in bridge monitoring system.